Nurturing families: A feasibility randomised controlled trial of a whole-family intervention with vulnerable families in Jordan - Brown, Felicity L.; Yousef, Hind; Bleile, Alexandra C.E.; Mansour, Hadeel; Barrett, Anna; Ghatasheh, Maha; Puffer, Eve S.; Mansour, Zeinab; Hayef, Karam; Kurdi, Samer; Ali, Qaasim; Tol, Wietse A.; et al. (Global mental health, 2024)
Armed conflict and forced displacement can significantly strain nurturing family environments, which are essential for child well-being. Yet, limited evidence exists on the effectiveness of family-systemic interventions in these contexts. We conducted a two-arm, single-masked, feasibility Randomised Controlled Trial (fRCT) of a whole-family intervention with Syrian, Iraqi and Jordanian families in Jordan. We aimed to determine the feasibility of intervention and study procedures to inform a fully-powered RCT. Eligible families were randomised to receive the Nurturing Families intervention or enhanced usual care (1:1). Masked assessors measured outcomes at baseline and endline; primary outcome measures were caregiver psychological distress, family functioning, and parenting practices. Families and implementing staff participated in qualitative interviews at endline. Of the 62 families screened, 60 (98%) were eligible, 97% completed the baseline and 90% completed the endline. Qualitative feedback indicated specific improvements in adolescent well-being, caregiver distress and parenting, and family relationships. Data highlighted high participant engagement and adequate facilitator fidelity and competence. Outcome measures had good psychometric properties (most α > 0.80) and sensitivity to change, with significant changes seen on most measures in the intervention but not control group. Findings indicate the acceptability and feasibility of intervention and study procedures. Subsequent full-scale evaluation is needed to determine effectiveness.